1991
DOI: 10.1055/s-2007-1019988
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Results Following Coronary Bypass Surgery Beyond the Age of 75 Years

Abstract: The indication for coronary bypass surgery in the elderly has been dramatically expanded in recent years. The results, however, are often contradictory. 1,538 consecutive patients undergoing cardiac surgery were divided into two groups by their age at the time of operation: younger than 75 years (n = 1,480) and 75 years and older (n = 58). These groups were compared with regard to influencing factors of early and late mortality, morbidity, and quality of life. Preoperatively, the clinical condition of the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…About 55% of all acute myocardial infarctions occur in the Medicare age group—that is, those over the age of 65 years 4 . Several studies found that younger (<65 years) and older (=65 years) patients report similar HRQL following cardiovascular surgery 15–17 . Yet other studies have shown that older age is associated with impaired HRQL in patients with CAD 18 and diabetes 19,20 .…”
mentioning
confidence: 99%
“…About 55% of all acute myocardial infarctions occur in the Medicare age group—that is, those over the age of 65 years 4 . Several studies found that younger (<65 years) and older (=65 years) patients report similar HRQL following cardiovascular surgery 15–17 . Yet other studies have shown that older age is associated with impaired HRQL in patients with CAD 18 and diabetes 19,20 .…”
mentioning
confidence: 99%
“…Çeşitli yayınlarda hastane mortalitesi %5.2-9.3 arasında değişmektedir (1,(3)(4)(5)(8)(9)(10). Yaşlı hastalarda yaygın arterioskleroz sık olduğun-dan operasyon esnasında perfüzyon basıncı yüksek tutulmamalı, 80-90 mmHg'nin altına düşürülmemelidir (12).…”
Section: Discussionunclassified
“…Bu yayınlarda yaşlılık için kriter 60-80 yaş arasında değişmektedir. Koroner bypass ameliyatlarının morbidite ve mortalite oranlarının yaş-lı hastalarda gençlere göre daha yüksek olduğu ifade edilmekledir (3,5,6,7). Bu çalışmada yaşlılık sınırı 65 yaş kabul edilerek, kliniğimizde koroner bypass ameliyatı yapılan 45 olgu retrospektif olarak gözden geçi-rildi.…”
Section: öZetunclassified
“…Multiple risk factors for atherosclerosis are established in CAD patients manifesting with myocardial infarction such as smoking [4] [5], family history [4]- [7], hypercholesteremia [5] [6], diabetes mellitus [4] [7], hypertension [4]- [6], obesity [5] [7], oral contraceptive utilisation in young females [8], cocain addiction [9], etc. Higher mortality and morbidity rates of coronary artery bypass surgery procedures in the elder patients is a matter of common knowledge in literatüre [10] [11]. We aimed to discuss preoperative risk factors and early postoperative results of 128 patients under 40 and over 80 years age executed coronary artery bypass surgery in our clinic under demographic values retrospectively.…”
Section: Introductionmentioning
confidence: 99%